Implementation of Children's Rights Execution In The Perspective of Civil And Islamic Law - January Nasya Ayu Taduri; Fairus Augustina Rachmawati; Dian Latifani (Faculty of Law, Merdeka University Surabaya, 2021)
Divorce or the breaking up of a marriage between husband and wife through a court decision has legal consequences for both parties' rights and obligations, including children. In Indonesia, cases that are often problematic in divorce cases are the failure to achieve the execution of decisions, especially in the context of the right to support the wife and children and child custody. However, in this paper, the author is interested in examining more deeply the obstacles that occur in implementing the execution of child custody decisions that are seen from several legal perspectives, including the compilation of Islamic law, the Marriage Law, the Child Protection Law, and the regulation of the execution process of decisions. in Herziene Inlandsch Reglement (HIR). The legal research method used is Normative Law with a statutory approach or called the statute approach. This paper also uses secondary legal data sources, such as: scientific journals, books, related laws and regulations. The purpose of this paper is to provide solutions related to the obstacles that occur in the implementation of decisions on the execution of child custody rights, which until now often occur and still provide polemics both in society and within the scope of religious and state courts.